Case report: Upper neck pouch sign in the antenatal diagnosis of esophageal atresia - Garg, Mukesh Kumar (Indian Journal of Radiology and Imaging, 2009)
Prenatal diagnosis of esophageal atresia remains a challenge for the imaging consultant. On antenatal USG, the finding of an absent or small stomach in the setting of polyhydramnios used to be considered suspicious of esophageal atresia. However, these findings have a low positive predictive value. The upper neck pouch sign is another sign that helps in the antenatal diagnosis of esophageal atresia. In this paper, I report a case of esophageal atresia that was diagnosed on USG at 27 weeks of gestation; the diagnosis was confirmed postnatally.
Keywords: Esophageal atresia; upper neck pouch sign